Analysis of Variance, Heritability, Correlation and Selection Character of M1 V3 Generation Cassava (Manihot esculenta Crantz) Mutants - Rahmi Henda Yani; Nurul Khumaida; Sintho Wahyuning Ardie; Muhamad Syukur (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Information about genetic variability and correlation between qualitative character and yield are important to support a selection program. The objective of this research was to determine genetic variability, heritability, and path analysis of M1 V3 cassava mutants’ characters. This research was conducted at Bogor Agricultural University Experimental Field Research from May 2014 to May 2015. This research used 32 mutants from five cassava parent lines which were Malang-4 and Adira-4 (national varieties), UJ-5 (Introduction variety from Thailand), and two local genotypes from Halmahera which were Jame-jame and Ratim. The results showed that gamma ray irradiation increased variability from five cassava genotypes. Characters that had high heritability were length of leaf lobe, lengthof petiole, stem diameter, and the height of plant. The path correlation analysis showed that number of tubers, number of economic tuber (> 20 cm), height to first branchingand stem diameter had direct correlation with tuber mass per plant. The characters can be used for the selection of M1 V4 generation.